Isomorphisms of combinatorial block decompositions of three-dimensional manifolds - Prishlyak, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For three-dimensional manifolds with the structure of a combinatorial block complex, we construct an invariant that allows one to verify the existence of isomorphisms, between these manifolds. For complexes of small dimensionality, we solve the problem on the possibility of extending the isomorphisms of subcomplexes to those of complexes.